Análise qualitativa e quantitativa da produção legislativa relacionada à saúde em tramitação no Congresso Nacional nos anos de 2007 e 2008 - Santos, Viviane Cristina dos [UNIFESP] (2011)
This dissertation had the objective to describe and analyse qualitatively and quantitatively the legislative production which deals with health, at the National Congress, happening in 2007 and 2008. It was done a descriptive-exploratory study with transverse cut and quantitative and qualitative approach. The material of analysis from the study was constituted by 112 draft bills which were performed at Social Security and family (House of representatives) and 32 draft bills at the Social Subjects (Federal Senate), related to health, which were performed from January 2007 to December 2008. The research had two distinctive phases, at the first phase there was a quantitative research through stratification, classification and analysis of the draft bills. At the second phase there was a qualitative approach made through a questionnaire containing closed questions to a specific group of professionals who performed in the Health System and the objective was to analyse the relevance, viability, strategic balance and impact of the selected projects. At the end of the study, the following results were found; from the 144 possibilities, 57,6% of the draft bills selected were presented in 2007 and 42,4% in 2008. The Labour Party, PT, was the one which most presented draft bills (12,5%) followed by PMDB (11,1%) and PSDB (10,4%). Only 25,7% of the Members of the Congress who presented draft bills deal with Health Policy. After a year of gathering the material to analyse the study, was verified that the majority of the draft bills (93,7%) were still being done, 4,9% were filed and only 1,4% were transformed in juridical norm. Considering the aim of the draft bills related to health, more than a half (57,7%) of the draft bills are related to the SUS ( Public Health Care ) and only 4,2% are related to quotation (financing for health). Considering the result of the applied questionnaire, 78,1% from the questioned people were dissatisfied, very dissatisfied with the Legislative Power and 41,8% classified as bad, extremely bad; at the private Health System only 9,6% considered bad, extremely bad. In relation to the criteria of the draft bills, more than a half (51,5%) from the questioned people declared that they did not understand, in the draft bills, the way of making viable what was proposed, 40,6% answered that there is no relevance; 52,7% answered there is not strategic balance from the draft bills to the priorities and the health policies of the country and 52,5% answered that the refusal of the draft bills would not bring negative impacts or would be prejudicial to the Brazilian society. Through a public enquire, more than a half (54,4%) answered they would approve the draft bill they analysed; 30,1% would not approve and 10,1% did not answer. Through the data of this study we can perceive that the Legislative production, related to health, is low; the members of the congress with academic graduation in the health area has a low output (25% of the amount) and the draft bills which become juridical norm is minimal (only 1,4% of the amount). It is important to point out the high rate of insatisfaction with the Legislative Power, with the Health Public Brazilian System and the low quality of the legislative production at the National Congress.